Limosilactobacillus reuteri administration alters the gut-brain-behavior axis in a sex-dependent manner in socially monogamous prairie voles - Donovan, Meghan; Mackey, Calvin S.; Lynch, Michael D. J.; Platt, Grayson N.; Brown, Amber N.; Washburn, Brian K.; Trickey, Darryl J.; Curtis, J. Thomas; Liu, Yan; Charles, Trevor C.; Wang, Zuoxin; Jones, Kathryn M. (Frontiers in Microbiology, 2023)
Research on the role of gut microbiota in behavior has grown dramatically. The probiotic Limosilactobacillus reuteri can alter social and stress-related behaviors – yet, the underlying mechanisms remain largely unknown. Although traditional laboratory rodents provide a foundation for examining the role of L. reuteri on the gut-brain axis, they do not naturally display a wide variety of social behaviors. Using the highly-social, monogamous prairie vole (Microtus ochrogaster), we examined the effects of L. reuteri administration on behaviors, neurochemical marker expression, and gut-microbiome composition. Females, but not males, treated with live L. reuteri displayed lower levels of social affiliation compared to those treated with heat-killed L. reuteri. Overall, females displayed a lower level of anxiety-like behaviors than males. Live L. reuteri-treated females had lower expression of corticotrophin releasing factor (CRF) and CRF type-2-receptor in the nucleus accumbens, and lower vasopressin 1a-receptor in the paraventricular nucleus of the hypothalamus (PVN), but increased CRF in the PVN. There were both baseline sex differences and sex-by-treatment differences in gut microbiome composition. Live L. reuteri increased the abundance of several taxa, including Enterobacteriaceae, Lachnospiraceae NK4A136, and Treponema. Interestingly, heat-killed L. reuteri increased abundance of the beneficial taxa Bifidobacteriaceae and butyrate-producing Blautia. There were significant correlations between changes in microbiota, brain neurochemical markers, and behaviors. Our data indicate that L. reuteri impacts gut microbiota, gut-brain axis and behaviors in a sex-specific manner in socially-monogamous prairie voles. This demonstrates the utility of the prairie vole model for further examining causal impacts of microbiome on brain and behavior.